KEPRIBADIAN MUSLIM TERHADAP PERILAKU BULLYING DI RUMAH SAKIT ISLAM WILAYAH KOTA PALEMBANG - Budiman Budiman; Eko Oktapiya Hadinata; Adi Apriatna (Psikis : Jurnal Psikologi Islami, 2017)
Purpose of the research to know the influence of Muslim Personality on Bullying Behaviours in Islamic Hospital of Palembang City Region. Some research that has been done in the West states that 56% of nurses become victims of bullying in their of workplacecausing harm to both individuals and organizations. The hypothesis of this research is that there is influence of Muslim personality on bullying behaviours in the workplace. The higher the comprehensionand practice of Muslim personality, the lower the occurrence of bullying behaviours in the workplace. This research using correlation research methods, research sample 214 nurses from 2 Islamic Hospital in Palembang, data collected using scalemethod, namely: Bullying Behaviour scale and Muslim Personality Scale and data analysis methods using simple regression analysis with SPSS programming. 22.5 for windows. Based on the results obtained r = 0.412in other word,there is influence of Muslim personality on bullying behaviours in the workplace. The higher the understanding and practice of Muslim personality, the lower the occurrence of bullying behaviours in the workplace and r2  of 0.170 means that 17% of Muslim personality contributed to bullying behaviours  in the workplace.